Examining the Best Candidate System in Promotion To Second-Echelon Positions in the Bureaucracy of the East Nusa Tenggara Provincial Government - Chatun, Sri (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study is a qualitative study with a descriptive approach and concluded with a SWOT analysis. The descriptive approach aims to describe one by one the main objects in this study, including echelon two ASN officials, SWOT analysis, rights, obligations, and responsibilities. The data used in this study are secondary data obtained by researchers from scientific articles, credible websites, and various other sources commonly used in research. The conclusion in this article show that the selection system for echelon two government officials, particularly in the East Nusa Tenggara region, is already sound. However, to improve it, the researcher suggests adding at least 10 percent local representation, as local representatives are more familiar with existing problems, are more familiar with local culture, and so on.